CT Analysis of the Posteromedial Fragment of the Posterior Malleolar Fracture. (June 2019) - Vosoughi, Amir Reza; Jayatilaka, Malwattage Lara Tania; Fischer, Benjamin; Molloy, Andrew P.; Mason, Lyndon W.
Background: To date, there have been no studies describing the characteristics of posteromedial fragment in the posterior malleolus fracture. The aim was to investigate the variability of posteromedial fracture fragments to enable better surgical planning. Methods: All Mason and Molloy type 2B fractures, defined as fracture of both the posterolateral and the posteromedial fragments of the posterior malleolus, from our database were identified to analyze the preoperative computed tomography scan. The posteromedial fragment was investigated in 47 cases (mean age, 46.6 years; 11 male, 36 female). Results: Morphologically, the fracture could be divided into 2 subtypes: (1) a large pilon intra-articular fragment (mean of X axis: 33.0 mm, Y: 30.7 mm, Z: 31.7 mm) presented in 29 cases with mean interfragmentary angle of 32.1 and back of tibia angle of 32.7 degrees (this was seen in 25 of 27 cases with supination injury pattern); and (2) a small extra-articular avulsion fragment (mean of X axis: 9.6 mm, Y: 13.2 mm, Z: 11.5 mm) present in 18 cases with a mean interfragmentary angle of 11.0 and back of tibia angle of 10.1 degrees. It was seen in 80% of pronation injuries. Conclusion: The avulsion type of the posteromedial fragment of posterior malleolus fracture was more common in pronation injuries, likely the result of traction by the intermalleolar ligament, and the pilon type was more common in supination injuries, likely the result of the rotating talus impaction. Because of the intra-articular involvement, we believe the pilon type should undergo fixation to achieve articular congruity, unlike the avulsion type which may only function as a secondary syndesmotic stabilizer. Level of Evidence: Level III, retrospective comparative series.